Evidenciar las oportunidades y retos que enfrentan los estudiantes de pregrado de ingeniería industrial de la universidad ECCI desde la academia y su contexto laboral (Memorias Sifored - Encuentros Educación UAN, 2023)
This article is the result of a degree project completed in the Industrial Process Management Technology program of the Industrial Engineering Department at ECCI University, Bogotá campus. Research articulated between two research groups "CASULOG" and "SITIC_IISP", linking the research lines Production, Logistics & Operations Analysis, and Management & Organizational Management with the intermediation of ICT respectively. The research is focused on the logistics of the customer management process required by the company Mundial de Mudanzas y Logística from the design of a technological tool, analyzing variables, definition, design, and development of a modular technological application (Jacob Brenkus, 2019). The descriptive and experimental methods are used, with the appropriate interpretation of the studied phenomenon (Grajales, 2000), allowing the identification of process engineering activities based on customer management. The collection of primary data was based on field techniques: observation and structured interviews with the management of the organization's management of the moving transportation service it provides (Garcia, 2006). By proposing the design of an information system hand in hand with integrated logistics, it optimizes the moving service to the place indicated by the client in a timely manner (Casanovas, A., & Cuatrecas, L., 2011).
Keywords: Teaching method innovations; Production Engineering; Information Technology; Computer Science; Educational Technology